Experience of hormone replacement therapy in postmenopausal women living with HIV. Issue 2 (June 2019) - Howells, P; Modarres, M; Samuel, M; Taylor, C; Hamoda, H
Objective: To assess the uptake of hormone replacement therapy in women living with HIV (WLHIV) in particular acceptability, response to treatment and compliance. Study design: Retrospective review of menopausal women attending a HIV medical gynaecology clinic in a tertiary referral London Hospital between 1 January 2011 and 31 December 2016. Main outcome measures: Patient demographics, presenting symptoms, uptake of hormone replacement therapy, type of hormone replacement therapy used and bone density assessment findings at presentation. Results: Seventy-three HIV patients were evaluated. Of them 64 (87%) were of black ethnicity and 9 (13%) were of white ethnicity. The commonest presenting complaints were vasomotor symptoms (40/73, (55%)) followed by low mood/irritability (20/73, (27%)). When offered hormone replacement therapy, this was accepted by 28/53 (52%) in WLHIV. The commonest regimen prescribed was transdermal oestradiol/micronised progesterone. A total of 22/24 (91%) women of black ethnicity reported good symptom control if they had started hormone replacement therapy, with 4/24 (17%) subsequently discontinuing it; 3/4 (75%) of white women reported good symptom control with hormone replacement therapy, with no one discontinuing it. The commonest reason for discontinuation was irregular bleeding. Of WLHIV who had a bone density assessment, 15/25 (60%) had osteopenia while 2/25 (8%) had osteoporosis. Conclusion: Our data show that only around 50% WLHIV accepted hormone replacement therapy when offered and a high proportion of these women discontinued it. Further research is needed to explore the reason leading to low uptake and high rates of stopping hormone replacement therapy. In addition, there is a need to increase awareness of the benefits of hormone replacement therapy in WLHIV both in the context of preventing osteoporosis and menopausal symptom management.